Projekfinansiering : die betekenis daarvan vir die finansiële instelling (2014)
D.Com. (Business Economics) === A clear distinction should be made between the straightforward financing of a project and project finance itself. In short, project finance can be defined as the financing of a particular economic unit with the aim of the financial structuring to be such that there is as little recourse as possible to the sponsor of the project and the lender is thus satisfied to look at the cash flows and earnings as the source of repayment and the assets of the project as security. Usually, project finance would incorporate all or some of the following characteristics namely, off balance sheet financing, recourse limited to the pre-commissioning stage, an element of fixed rate debt, utilisation of tax allowances, optimisation of tax position, long term finance and some degree of foreign exchange activity. If the project is sponsored by an existing company, it will be looking to maximise debt, minimise recourse and group tax liability, optimise financial costs and retain or improve financial ratios after consolidation of the project. However, the degree of project financing appropriate for any project depends on what lenders are prepared to accept and what sponsors are prepared to provide in order to let the project become a reality. The project financier's role is to formulate financial structures, assess financial feasibility, develop funding proposals, secure sources of finance and to manage the financing facilities once they are in place. A project sponsor employs a project financier because the latter is objective, impartial, has access to required information and is able to process it into a professional presentation to the financial community, has the experience and expertise to advise on the most appropriate and cost effective financing structure and is best equipped to perform a thorough project financial analysis. This study has been undertaken to point out the differences between project finance and finance for a project, to identify the role of project financier and is as such largely concentrated on the financial side of a project. The goal was to discuss the importance of project finance from the financial institutions' viewpoint and to identify those aspects that would be important to a project advisor or lender. Although relatively little has been published on project finance, it is a multidisciplinary subject and references have been used wherever available. The author's attendance at seminars on the subject, as well as discussions with international project financiers and bankers have also contributed to the understanding of the subject. In addition to an in-depth exposure to project finance in South Africa, several months have been spent with an international bank's project finance division in London.